Ipsilateral distal femoral and proximal tibial epiphyseal growth plate injury: a case report - Gulabi, Deniz (BioMed Central, 2013)
INTRODUCTION: Both the isolated distal femoral epiphysiolysis and the isolated proximal tibial epiphysiolysis are the least common epiphyseal injuries. Even though they are uncommon, they have a high incidence rate of complications. CASE PRESENTATION: We present a case with Gustilo-Anderson grade 3b open and Salter-Harris type 1 epiphysiolysis of the distal femur and proximal tibia caused by a farm machinery accident. The patient was a 10-year-old boy, treated by open reduction and internal fixation. CONCLUSION: Although distal femoral and proximal tibial growth plate injuries are rarely seen benign fractures, their management requires meticulous care. Anatomic reduction is important, especially to minimize the risk of growth arrest and the development of degenerative arthritis. However, there is a high incidence of growth arrest and neurovascular injury with these type of fractures.